2014
DOI: 10.3233/jad-141116
|View full text |Cite
|
Sign up to set email alerts
|

A Global Immune Deficit in Alzheimer's Disease and Mild Cognitive Impairment Disclosed by a Novel Data Mining Process

Abstract: Alzheimer's disease (AD) is the most common form of dementia, while mild cognitive impairment (MCI) causes a slight but measurable decline in cognitive abilities. A person with MCI has an increased risk of developing AD or another dementia. Thus, it is of medical interest to develop predictive tools to assess this risk. A growing awareness exists that pro-oxidative state and neuro-inflammation are both involved in AD. However, the extent of this relationship is still a matter of debate. Due to the expected non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Persistent central nervous system (CNS) inflammation is associated with, and may even predispose individuals to, many neurodegenerative diseases. [6][7][8] Moreover, neuroinflammation is recognized as a major component of several neurocognitive and psychological disorders, including Alzheimer disease, major depressive disorder, and schizophrenia. 9,10 How inflammation contributes to neurocognitive impairment is not completely clear; however, several inflammation-associated factors, including cytokines, chemokines, and reactive oxygen and nitrogen species from activated microglia can directly and/or indirectly promote neuronal injury or death.…”
mentioning
confidence: 99%
“…Persistent central nervous system (CNS) inflammation is associated with, and may even predispose individuals to, many neurodegenerative diseases. [6][7][8] Moreover, neuroinflammation is recognized as a major component of several neurocognitive and psychological disorders, including Alzheimer disease, major depressive disorder, and schizophrenia. 9,10 How inflammation contributes to neurocognitive impairment is not completely clear; however, several inflammation-associated factors, including cytokines, chemokines, and reactive oxygen and nitrogen species from activated microglia can directly and/or indirectly promote neuronal injury or death.…”
mentioning
confidence: 99%
“…Four genes identified in the pathway analysis (ESR1, PHB, RYR3, GRIK2) constitute part of an immunologic signature in the MSigDB database 39 that was identified as significantly associated with the cognitive impairment phenotype. Both the individual genes that comprise this signature, and innate and adaptive immunity as biological processes have been associated with cognitive impairment and cognitive aging [40][41][42][43][44][45][46] . Polymorphisms in estrogen receptor genes (ESR1 and ESR2) have been associated with risk of developing cognitive impairment and in turn may play a role in cognitive aging 42,47 .…”
Section: Discussionmentioning
confidence: 99%
“…This is an adaptive mathematical model widely applied to study various pathological conditions, as particularly suitable for analyzing non-linear interactions between many variables [30,32,[35][36][37][38][39]. Unlike standard statistical tests, ANNs is also a valid tool to analyze small sized samples, with imbalance between variables and records [38,39].…”
Section: Artificial Network Analysismentioning
confidence: 99%
“…The semantic connectivity map is a data mining approach maintaining the links among variables, and enabling the detection of hidden trends and associations. It has been demonstrated that this method might be the future of data analysis in many areas of medicine, as it can improve the predictive value of classic statistics [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%